Research progress in treatment of rheumatoid arthritis with Sinomenine and related formulations based on different administration routes - Wang, Wenya; Wang, Zihui; Ling, Aixia; Zhang, Chunyan; Lv, Mei; Huang, Lufen; Niu, Yanlian (Frontiers in Pharmacology, 2025)
Sinomenine (SIN), a multi-target alkaloid extracted from Sinomenium acutum, demonstrates significant immunomodulatory, anti-inflammatory, and osteoprotective properties in the treatment of rheumatoid arthritis (RA). It achieves these effects by modulating immune cells, such as macrophages and T cells, suppressing pro-inflammatory cytokines like tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6), and inhibiting synovial hyperplasia and bone erosion. Recent advancements in drug delivery systems (DDSs), including oral sustained-release formulations, transdermal microneedles, lipid-based carriers (such as transfersomes and ethosomes), and intra-articular thermosensitive hydrogels, have markedly improved its bioavailability, targeting precision, and therapeutic longevity. For example, reactive oxygen species-responsive microneedles and biomimetic nanocarriers facilitate spatiotemporal-controlled drug release, while hybrid exosome-liposome systems enhance synovial retention and minimize systemic toxicity. Although preclinical results are promising, challenges like incomplete clinical validation, limited exploration of combination therapies, and inadequate adaptation to RA’s dynamic microenvironments persist. Future research should focus on developing intelligent DDSs with multi-stimuli responsiveness, leveraging omics for mechanistic insights, and creating patient-specific delivery strategies to enhance clinical application. This review highlights SIN’s transformative potential in RA management and calls for interdisciplinary collaboration to improve its translational success.